DINAMIKA KEKERASAN TERHADAP SISWI DI SEKOLAH - Sudaryanto Sudaryanto; Surya Dailiati; Hernimawati Hernimawati; Tesya Aulia Balqis (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
Schools, as formal learning venues, must be safe and comfortable spaces free from various human rights violations, including violence against women (female students). Setia Sharma High School, Pekanbaru City, is committed to protecting women. Communication with the school and input from the educational institution indicates that education and training on violence against women/female students is necessary, as it has been lacking. Setia Dharma High School requires collaboration with various parties to achieve the school's vision and mission. Setia Dharma High School, Pekanbaru City, needs partners to protect female students from violence. The school still needs to improve its understanding of knowledge, actions, and solutions related to violence against women. Therefore, it is necessary to provide information on the dynamics of violence against women. The community service program involves providing counseling to teachers, staff, and students. The school has responded positively to this service activity. Students are not only thinking about how to achieve their future by continuing their education or pursuing a career, but also about protecting themselves at all times, wherever and whenever. Keywords: Violence, Women, School